FOMO (Fear Of Missing Out) Tren Fashion Sebagai Gaya Hidup Mahasiswa Ilmu Komunikasi - Annisa, Kerin Gusvira; Juliana Kurniawati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
This research aims to find out how the phenomenon of FOMO (fear of missing out) fashion trends as part of a lifestyle based on the perceptions of Communication Science students at Universitas Muhammadiyah Bengkulu. The FOMO phenomenon is triggered by the use of social media which encourages students to always keep up with fashion trends. This research uses qualitative research methods with a phenomenological approach. The theory used is the S-O-R theory (Stimulus-Organism-Response) by Hovland (1953), which explains that the stimulus or stimulus comes from the external in the form of fashion trends on social media, then processed internally in the form of attention, understanding, acceptance by students so as to produce a response in the form of behavior following the trend. The results showed that Communication Science students interpret fashion trends as a means to build self-image, increase self-confidence, self-comfort, and maintain existence on social media.